Curiositas altissima - Ioana Costa (Revista de Istorie și Teorie Literară)
The works written by Dimitrie Cantemir in Latin language are meant to respond to the curiosity the author assumes that characterizes his readers. He accomplishes his purpose in a multifarious manner, mostly by offering precise data extracted from an extensive bibliography. Nonetheless, his personal experience is frequently a valuable source. He enhances his knowledge by experiments and autoptic observations, revealing himself both as a truthful (and inspired) author and as a scholar that embraces the world with an acute sense of scientific curiosity.